Advance Arabic grammar for academic purposes (part one-nominal sentence) - Dollah, Nafi@Hanafi (2004)
This is a book in advanced Arabic grammar for scientific purposes (NOMINAL SENTENCE) - a study in the nominal sentence - we call upon him to present an advanced style of literature in a way that takes into account a set of fundamentals that provide the student with the opportunity to assimilate the Arabic grammatical system in its advanced level. During a scientific study documented the structure of the word Arab structures and the nominal analysis of its components. The Objectives of the Disclosure are to introduce the students to a true scientific concept of the Arabic nominal structures and to follow the origins of the old grammar as we follow the theories of modern linguistics and achieved a pairing between the old and the new as well as to develop the nominal sentence structure and indications and offers through the evidence of the rich Koran.